The Reconstruction of High-Inherited Wealth in Minangkabau through Cash Waqf Movement - Eficandra Eficandra (Institut Agama Islam Negeri Batusangkar, 2022)
The development and demands of modern life results in the decrease of role and existence of high-inherited wealth in Minangkabau. This fact requires a reconstruction of the development of high-inherited wealth in Minangkabau. One of them is through cash waqf movement which is an alternative in developing and empowering the people’s economy. This paper aims at explaining the reconstruction of high-inherited wealth in Minangkabau through the cash waqf movement. This study tried to offer solutions and alternatives in restoring the role and existence of high-inherited wealth in Minangkabau through the cash waqf movement. By using a qualitative approach, this study found that the cash waqf movement can restore the role and position of high-inherited wealth in Minangkabau in the following forms; first, returning or reclaiming the pawned assets and increase the number of assets through the cash waqf movement from all members of the tribe or clan. Second, striving for the legality of these assets by changing the certificate into waqf property. Third, managing the high-inherited assets productively and share the profits for the economic needs and welfare of the people or tribe. Assets management and development through the cash waqf movement can be used as a model for other communities, especially the Minangkabau community in managing people’s or tribal assets and improving the welfare of the people.